2016
DOI: 10.1080/00423114.2016.1193209
|View full text |Cite
|
Sign up to set email alerts
|

Connected cruise control: modelling, delay effects, and nonlinear behaviour

Abstract: Connected vehicle systems (CVS) are considered in this paper where vehicles exchange information using wireless vehicle-to-vehicle (V2V) communication. The concept of connected cruise control (CCC) is established that allows control design at the level of individual vehicles while exploiting V2V connectivity. Due to its high level of modularity the proposed design can be applied to large heterogeneous traffic systems. The dynamics of a simple CVS is analysed in detail while taking into account nonlinearities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 238 publications
(135 citation statements)
references
References 38 publications
1
134
0
Order By: Relevance
“…In the context of platoon stability, it has been shown that well-placed, communicating autonomous vehicles may be used to stabilize platoons of human-driven vehicles [30]. More generally, the platooning problem has been studied as a consensus problem with delays [31].…”
Section: A Related Work On Car-following Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of platoon stability, it has been shown that well-placed, communicating autonomous vehicles may be used to stabilize platoons of human-driven vehicles [30]. More generally, the platooning problem has been studied as a consensus problem with delays [31].…”
Section: A Related Work On Car-following Modelsmentioning
confidence: 99%
“…We now illustrate the boundary for the region of non-oscillatory convergence of the MOVM described by (30). In order to better-understand the stringent constraints on system parameters to achieve non-oscillatory convergence, we also plot the necessary and sufficient condition for local stability (22) of the MOVM.…”
Section: Non-oscillatory Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…However, in real traffic situations, not all vehicles are equipped with range sensors and since the range of V2V communication is limited, the data about leader's motion might not be accessible to every member of the vehicular string. Therefore, the concept of connected cruise control (CCC) was introduced in [18], [22], and [23], where all available V2V signals are utilized. This concept is applicable even in the presence of human-driven vehicles in the string and it can be used in realistic traffic scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…However, this architecture is not practical for real traffic situations since the probability that multiple radar equipped vehicles travel next to each other is very small, and all vehicles talking to a leader is not possible due to the limited range of V2V communication. Thus, the concept of connected cruise control (CCC) was established in Orosz (2014); Ge and Orosz (2014) which uses all available V2V signals when inserted into a flow of human-driven vehicles. CCC may be used to support the human driver, to supplement sensory information, or to control the longitudinal motion of vehicle.…”
Section: Introductionmentioning
confidence: 99%